Identification of Bacteria in Dental Plaque - Syahdiana Waty; Nurul Hidayah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Oral health has an important role in overall body health. This study aims to evaluate the antibacterial efficacy of toothpaste with cinnamon ethanol extract against Streptococcus bacteria in vivo, analyze changes in the number of bacterial colonies before and after using toothpaste, and identify the type of Streptococcus bacteria in dental plaque. This pure experimental research was conducted at the Pharmacy Laboratory of the Poltekkes Kemenkes Medan and the Microbiology Laboratory of the Faculty of Medicine, University of North Sumatra. Samples included cinnamon extract, toothpaste formulation with 12.5% extract concentration, and dental plaque from 40 respondents. Data analysis used descriptive univariate test with SPSS 22.0 application. Results showed Gram-positive bacterial infections, especially Rothia dentocariosa (24%), dominated dental plaque, followed by Streptococcus mitis (16.4%). The use of cinnamon-active toothpaste was able to significantly reduce the number of bacterial colonies, especially at high concentrations. In addition, active compounds in cinnamon extracts such as cinnamaldehyde and eugenol showed the ability to damage bacterial cell walls and inhibit biofilm formation. Gargling was also shown to be effective in reducing bacterial colonies by clearing plaque and food debris. The conclusion of this study suggests that Gram-positive bacterial infections in dental plaque require special attention in management with appropriate antibiotics, while gargling and the use of cinnamon-based antimicrobial agents can be an effective preventive strategy. These findings support the development of natural ingredient-based oral health products to improve infection prevention and the quality of oral health care. Keywords: Oral Health, Streptococcus, Cinnamon, Antibacterial, Dental Plaque, Gargling